CARING FOR CHILDREN WITH THE AIM OF THEIR HEALTHY DEVELOPMENT IN ADULTHOOD - Karimova. M. (Galaxy International Interdisciplinary Research Journal, 2022)
The article opens the process of personality formation of certain skills and abilities, the necessary knowledge, personal qualities, creative abilities. The main goal of education is aimed at personality formation.